THE ROLE OF THE TAVIP BINJAI MARKET AS A DISTRIBUTION CENTER FOR LOCAL AGRICULTURAL PRODUCTS IN BINJAI, NORTH SUMATRA - Nasti Hasyim Nasution; Abdi Sugiarto; Ruri Prihatini Lubis (Bulletin of Engineering Science, Technology and Industry, 2025)
Tavip Market Binjai is one of the main markets in Binjai City, North Sumatra, with a strategic role in the distribution of local agricultural products. This study aims to analyze the role of Tavip Market Binjai in distributing agricultural products, identify factors influencing distribution effectiveness, and formulate strategies to enhance the market's efficiency as a distribution center. The research employed both qualitative and quantitative approaches, using data collection techniques such as observation, interviews, and literature reviews. The findings indicate that Tavip Market Binjai serves as a central hub for trade and distribution for local farmers, contributes to price stability, increases income for farmers and MSMEs, and supports food security in Binjai and surrounding areas. However, distribution effectiveness in this market is still affected by several constraints, including limited infrastructure, suboptimal logistics systems, reliance on intermediaries, and competition from imported products. To address these challenges, the study recommends several strategies, including improving market infrastructure, optimizing transportation and logistics systems, strengthening the role of cooperatives and partnerships, using digital marketing technology, and implementing regulations that support price stability and protect local products. With the implementation of appropriate strategies, it is expected that Tavip Market Binjai can be more effective in supporting the distribution of local agricultural products, thus providing greater economic benefits to farmers, traders, and the community as a whole.